Direct specification of lymphatic endothelium from mesenchymal progenitors - Lupu, I; Grainger, DE; Kirschnick, N; Weischer, S; Zhao, E; Martinez-Corral, I; Schoofs, H; Vanhollebeke, M; Jones, G; Godwin, J; Forrow, A; Lahmann, I; et al. (Springer Nature [academic journals on nature.com], 2025)
During embryogenesis, endothelial cells (ECs) are generally described to arise from a common pool of progenitors termed angioblasts, which diversify through iterative steps of differentiation to form functionally distinct subtypes of ECs. A key example is the formation of lymphatic ECs (LECs), which are thought to arise largely through transdifferentiation from venous endothelium. Opposing this model, here we show that the initial expansion of mammalian LECs is primarily driven by the in situ differentiation of mesenchymal progenitors and does not require transition through an intermediate venous state. Single-cell genomics and lineage-tracing experiments revealed a population of paraxial mesoderm-derived Etv2+Prox1+ progenitors that directly give rise to LECs. Morphometric analyses of early LEC proliferation and migration, and mutants that disrupt lymphatic development supported these findings. Collectively, this work establishes a cellular blueprint for LEC specification and indicates that discrete pools of mesenchymal progenitors can give rise to specialized subtypes of ECs.